The effects of the urotensin-II receptor antagonist palosuran treatment on the corpora cavernosa of streptozotocin-induced diabetic rats - Murat Olukman; Cenk Can; Sibel Ülker; Yiğit Uyanikgil; Türker Çavuşoğlu; Neslihan Düzenli; Deniz Coşkunsever; Fatma G. Kozcu (Asian Journal of Urology)
Objective: This study aimed to investigate the effects of treatment with palosuran, a urotensin receptor blocker, on molecular changes in the corpora cavernosa (CC) in diabetic rats. Methods: Streptozotocin-induced diabetic rats were treated with palosuran 300 mg/kg per day for 6 weeks. Contraction of CC induced by potassium chloride, phenylephrine, and NG-nitro-L-arginine methyl ester and relaxation of CC induced by electrical field stimulation (EFS) and sodium nitroprusside (SNP) (endothelium-dependent and endothelium-independent stimuli, respectively), and Y-27632 (Rho-kinase inhibitor) were examined in organ baths. Direct contraction or relaxation induced by palosuran and urotensin-II (U-II) were also evaluated. The expression levels of nitric oxide synthetases (NOSs), RhoA, oxidative stress regulators, and U-II were analyzed by Western blotting or immunohistochemistry. Results: Induction of diabetes in rats resulted in the decreased relaxant response to SNP, decreased pD2 value of SNP, attenuated relaxant response to Y-27632 as well as the decreased RhoA expression in CC. Palosuran treatment of diabetic rats reversed all of these parameters; however, it further impaired the already weakened relaxation of diabetic CC in response to EFS. Although induction of diabetes did not change U-II expression in CC significantly, palosuran treatment reduced U-II expression in diabetic CC. The expression level of nNOS was lowered in diabetic CC; however, palosuran treatment did not change the decreased the neuronal NOS expression. In vitro exposure of diabetic CC strips to palosuran produced a direct relaxant response. Conclusion: Palosuran treatment did not affect the expression of NOSs or reduce nitrergic conduction induced by EFS stimulation in diabetic CC. However, while directly triggering a relaxant response, it did not induce a prominent contraction either by decreasing U-II expression, or increasing the sensitivity of CC to nitric oxide which suggested that palosuran has the potential to support erectile function. Further and comprehensive studies are required to clarify this issue.